MENUMBUHKAN CINTA LITERASI MELALUI MENULIS KREATIF SISWA MA DARUSSALAM KECAMATAN BARAMBAI-BATOLA - Jamiatul Hamidah; Akhmad Syakir; M. Subhan Wiranata (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2019)
The low interest in reading and writing students because of the easier access to the internet and the rapid flow of technology that reaches into the countryside. This results in MA Darussalam students who prefer watching, playing games, and playing social media than reading books or writing literary works. This creative writing training activity aims to foster interest in reading and writing adolescents, especially MA students, fostering language skills for MA students, especially in terms of creative writing, contributing knowledge in the field of language skills to the community in Batola District. This community service method is carried out by giving lectures to students about the importance of reading and writing culture and material about creative writing. Then students are trained to write short stories based on their daily experiences. The results of this activity showed a very good response from students and increased student interest in reading and writing. Evidenced by the many questions asked by students in the question and answer session, increased student knowledge about literacy culture, and requests from students and schools so that this activity continues on a regular basis.